Identification of a novel nicotinic acetylcholine receptor structural subunit expressed in goldfish retina (The Rockefeller University Press, 1989)
A new non-alpha (n alpha) member of the nicotinic acetylcholine receptor (nAChR) gene family designated GFn alpha-2 has been identified in goldfish retina by cDNA cloning. This cDNA clone encodes a protein with structural features common to all nAChR subunits sequenced to date; however, unlike all known alpha-subunits of the receptor, it lacks the cysteine residues believed to be involved in acetylcholine binding. Northern blot analysis shows multiple transcripts hybridizing to the GFn alpha-2 cDNA in goldfish retina but undetectable levels of hybridizable RNA in brain, muscle, or liver. S1 nuclease protection experiments indicate that multiple mRNAs are expressed in retina with regions identical or very similar to the GFn alpha-2 sequence. In situ hybridization shows that the gene encoding GFn alpha-2 is expressed predominantly in the ganglion cell layer of the retina.